A new Asian subgenus and species of Ischalia (Coleoptera: Ischaliidae) with an assessment of subgeneric concepts, revised world checklist, and keys to the subgenera and “blue elytra” species - Young, Daniel K. (Zootaxa, 2011)
A new subgenus of Ischalia, Nitidischalia, and new species, Ischalia (Nitidischalia) barclayi, is described and illustrated from Sabah, Malaysia. Subgeneric concepts are discussed and an updated world checklist of subgenera and species is presented. A revised key to the Southeast Asian Ischalia species exhibiting blue elytra is also presented, as is a key to the subgenera of Ischalia.